Morphine as first medication for treatment of cancer pain - Beatriz C. Nunes; João Batista dos Santos Garcia; Rioko Kimiko Sakata (Brazilian Journal of Anesthesiology, 2014)
Background and objectives: the medications used according to the recommendation of the World Health Organization do not promote pain relief in a number of patients with cancer pain. The aim of this study was to evaluate the use of morphine as first medication for the treatment of moderate cancer pain in patients with advanced and/or metastatic disease, as an option to the recommendations of the World Health Organization analgesic ladder. Method: sixty patients without opioid therapy, with ≥18 years of age, were randomized into two groups. G1 patients received medication according to the analgesic ladder and started treatment with non-opioids in the first, weak opioids in the second, and strong opioids in the third step; G2 patients received morphine as first analgesic medication. The efficacy and tolerability of initial use of morphine were evaluated every two weeks for three months. Results: the groups were similar with respect to demographic data. There was no significant difference between the groups regarding pain intensity, quality of life, physical capacity, satisfaction with treatment, need for complementation and dose of morphine. In G1 there was a higher incidence of nausea (p = 0.0088), drowsiness (p = 0.0005), constipation (p = 0.0071) and dizziness (p = 0.0376) in the second visit and drowsiness (p = 0.05) in the third. Conclusions: the use of morphine as first medication for pain treatment did not promote better analgesic effect than the ladder recommended by World Health Organization, with higher incidence of adverse effects. Resumo: Justificativa e objetivos: Os medicamentos usados segundo a recomendação da Organização Mundial de Saúde (OMS) não promovem alívio da dor de uma parcela dos pacientes com dor oncológica. O objetivo deste estudo foi avaliar o uso de morfina como primeiro medicamento para o tratamento da dor oncológica moderada, em pacientes com doença avançada e/ou metástases, como opção às recomendações da escada analgésica preconizada pela OMS. Método: Sessenta pacientes sem terapia com opioide, com idade maior ou igual a 18 anos, foram distribuídos aleatoriamente em dois grupos. Os pacientes do G1 receberam medicamentos segundo a escada analgésica e iniciaram o tratamento com não opioide no primeiro degrau, opioide fraco no segundo e opioide potente no terceiro; os do G2 receberam morfina como primeiro medicamento analgésico. Foram avaliadas a eficácia e a tolerabilidade do uso inicial de morfina, a cada duas semanas durante três meses. Resultados: Os grupos foram semelhantes quanto aos dados demográficos. Não houve diferença significante entre os grupos quanto à intensidade da dor, qualidade de vida, capacidade física, satisfação com o tratamento, necessidade de complementação e dose de morfina usada. No G1 houve maior incidência de náusea (p = 0,0088), sonolência (p = 0,0005), constipação (p = 0,0071) e tontura (p = 0,0376) na segunda consulta e para sonolência (p = 0,05) na terceira. Conclusões: O uso de morfina como primeiro medicamento para tratamento da dor não promoveu melhor efeito analgésico do que a escada preconizada pela OMS e houve maior incidência de efeitos adversos. Keywords: Cancer pain, Analgesia, Morphine, Palavras-chave: Dor oncológica, Analgesia, Morfina